ANALISIS MEKANISME KERJA SAMA USAHA AYAM POTONG MENURUT TINJAUAN EKONOMI ISLAM - Nova Haryani; Ismaulina Ismaulina; Nurul A'la (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2019)
This study aims to determine the mechanism of cooperation between the business of broiler chicken in Blang Raleue Village, Simpang Kramat Subdistrict. Overview of the Islamic Economy on the mechanism of cooperation between the business of the three-broiler chicken in Blang Raleue Village, Simpang Kramat Sub-district. This research is a descriptive qualitative study. To obtain data the author uses observation and interview techniques. The type of data used is primary data obtained directly from the business owner of the three-piece broiler chicken in Blang Raleue Village, Simpang Kramat District. Secondary data obtained from notes, books, journals and others related to the problems that the authors examine. The data analysis method used is descriptive qualitative, namely data collection, data presentation, and conclusion drawing. The results of this study indicate that the contents of the cooperation contract in the three-broiler chicken farm in the Blang Raleue Village of Simpang Kramat Subdistrict have not fully complied with the syirkah concept. But there are also some contents of the cooperation contract that are in accordance with the concept of syirkah.